The Effect of Company Characteristics Towards Carbon Emission Disclosure and Its Impact on Economic Consequences in Non-Financial Registered Companies in Indonesia, Malaysia, Thailand and The Philippines Period For 2008-2017 - Gatot Nazir Ahmad; Roh Ajiasri; Ari Warokka (LPPM Universitas Negeri Jakarta, 2020)
This research was conducted to know the company's characteristics, the determining factors for the disclosure of carbon emissions, and the impact of the disclosure of carbon emissions on economic consequences. The financial result in this study is the decision-making behavior of businesses, governments, and creditors as a result of accounting reporting, in this case, environmental disclosures contained in annual reports and sustainable reports. This study's sample amounted to 45 companies registered in Indonesia, Malaysia, Thailand, and the Philippines, with an observation period of 2008 to 2017. To measure the disclosure of carbon emissions by creating a checklist based on information from the CDP. Company characteristics are proxied by profitability, leverage, size, and sales growth, while economic consequences are proxied by the bid-ask spread, trading volume, and stock price volatility. The analytical method used in this study is the Partial Least Square (PLS) method using the WARP PLS version 5.0 application. From the test results, it was found that Profitability and Size had a positive effect on disclosure of carbon emissions, growth sales had a negative effect, and leverage had no effect. Meanwhile, the impact of disclosing carbon emissions on the bid-ask spread, trading volume, and stock price volatility has a positive effect.